Cardiovascular risk factors found in stroke patients - Novo, André (2014)
Were analyzed 346 patients with ischemic stroke (78.6±9.9 years) and 96 with intracerebral hemorrhage (76.5±11.9 years). In ischemic stroke the most common risk factors were hypertension (68.2%), diabetes mellitus (27.5%), hypercholesterolemia (25.0%), atrial fibrillation (24.3%) and smoking (5.5%). We also found that 12.7% of the patients were obese. In hemorrhagic stroke the most prevalent risk factors were hypertension (53.1%), dyslipidemia (25.7%), atrial fibrillation (24.3%), obesity (18%) and smoking (7.3%). Hypertension was more prevalent in ischemic stroke and is associated with type of stroke (x2 = 7.508, df = 1, p = 0.005). Atrial fibrillation also prevailed in thromboembolic events with statistical significance (p = 0.043). Only 16% of patients with ischemic stroke did not have any cardiovascular risk factor.